Discussion Board Tool and Student Engagement in a Digital Learning Space - Samuel Adeyinka-Ojo (Tecno Scientifica Publishing, 2021)
The purpose of this paper is to share the author’s online teaching experiences on increasing student engagement and learning experience in a digital teaching environment using the discussion board tool. This paper was written in the first person – that is, the author as I positioned myself within the study context. Blackboard was adopted as the learning management system at the author’s affiliated university for the digital teaching and learning delivery during the COVID-19 pandemic era. Discussion board is a communication tool contained within the Blackboard Collaborate Ultra that can be used to enhance learning and teaching. This paper is a reflective account of the author and students in three undergraduate (UG) teaching units during pandemic era. A combination of existing academic literature, online resources, online interviews via discussion board tool and personal experiences were employed to demonstrate and reflect my engagement with UG students in order to achieve specific learning outcomes. To achieve the purpose of my personal reflection reporting, this study asks one question from the participants: How would you describe your learning experience and engagement with your lecturer and fellow students using the discussion board tool for pre-tutorial and group assignment? This paper presents a context, reflection and case scenarios of three UG teaching units concerning fostering student engagement in digital learning environment through the discussion board tool. Findings indicate that there are three stages of student engagement using the discussion board tool namely: tutor-student engagement, student-student engagement, and student group-student group engagement. Discussion board tool encourages active learning experience. The implications of my reflective account shows that fostering student engagement in a digital learning environment through the discussion board is important for both tutors and students. It is recommended that more faculty members will explore learning and teaching resources available on discussion board tool in the ‘new normal’ era.